Does publication of interest rate paths provide guidance - Gisle James Natvik; Dagfinn Rime; Olav Syrstad (Norges Bank, 2019)
Does the central bank practice of publishing interest rate projections (IRPs) improve how market participants map new information into future interest rates? Using high-frequent data on Forward Rate Agreements (FRAs) we compute market forecast errors; differences between expected future interest rates and ex post realizations. We assess their change in narrow windows around monetary policy announcements and macroeconomic releases in Norway and Sweden. Overall, communication of future policy plans do not improve markets' response to information, irrespective of whether or not IRPs are in place. A decomposition of market reactions into responses to the current monetary policy action ("target") and responses to signals about the future ("path"), reveals that only policy actions lead to improvements in market forecasts.
hdl:11250/2652984
Keywords: D72; O13; Q33; 330; monetary policy; interest rate paths; forward guidance; high-frequency data; forecasts